Venous ligation versus venous repair: does the procedure impact venous thromboembolism risk?. Issue 1 (18th March 2021) - Farrell, Michael Steven; Knudson, M Margaret; Stein, Deborah M
Abstract : Background: Traumatic lower extremity venous injuries are most commonly managed with either a vein ligation or repair procedure. Venous injuries are associated with an increased risk of developing venous thromboembolisms (VTE), but little is understood with regard to how specific surgical treatments may impact the risk of developing either a deep vein thrombosis (DVT) or a pulmonary embolism (PE). In this study of lower extremity venous injuries, we hypothesized that venous ligation would be associated with an increased risk of DVT but a lower risk of PE when compared with venous repair. Methods: Patients were identified from the National Trauma Data Bank (2008 to 2014) with at least one iliac, femoral, popliteal, or tibial venous injury and who received either a vein ligation or repair. The patients were then compared based on the type of procedure and the location of the injury to assess the risk of DVT and PE between the groups. Results: A total of 1214 patients were identified. There was no difference between patients who received a vein ligation versus a repair with respect to age, injury severity score, or initial systolic blood pressure. There was no difference in the odds of developing either a DVT or PE between patients who were treated with vein ligation versus repair. There was also no difference in VTE rates when stratified by the location of the injury. Conclusions: In individuals with lower extremity venous injuries, there is no difference in the rate of DVT or PE complications when comparing venous repair and ligation procedures. The role of anticoagulation remains to be elucidated following operative treatment. Level of evidence: Therapeutic/Care Management, Level IV.